Western Australian women's perceptions of the style and quality of midwifery postnatal care in hospital and at home - Fenwick, J.; Butt, Janice; Dhaliwal, Satvinder; Hauck, Yvonne; Schmied, V. (Elsevier, 2010)
Summary. Aim and background: An important part of maternity service provision is the care provided by midwives in the immediate postpartum period. Evidence suggests that postpartum morbidity and its impact on women's health after childbirth is an area of genuine concern. In Western Australia there is limited information on women's postpartum health needs and/or the quality of midwifery care provided in hospital and at home. This paper describes Western Australian (WA) women's perceptions of midwifery care in the early postpartum period. Method: A cross-sectional, self report survey was used to describe the practical, emotional and informational support provided by midwives in the initial postpartum period. A questionnaire, specially designed for this population, was posted at 8 weeks postpartum to every woman with a registered live birth in WA between February and June 2006. Completed questionnaires were received from 2699 women. Datawere analysed using descriptive statistics, t-tests and chi-squared. Results: Results indicate that overall, women were happy with most aspects of midwifery carerelated to practical advice and assistance in relation to baby care and their immediate physical recovery. Areas that received a less positive rating were related to providing consistent advice, availability of the midwife, emotional care and information on maternal health needs, immunisation and contraception. In general, first time mothers rated both the style and quality of care more negatively than multiparous women. There was a trend by women accessing private hospital care to rank their care less favourably. There were minimal differences noted between women in metropolitan and non-metropolitan areas. Midwifery care at home was rated very positively and significantly better than hospital care (p < 0.002).Conclusion: Although the majority of women in this study were satisfied with the components of physical care and information and assistance with infant feeding and sleep and settling provided in the short-term, there was less satisfaction with emotional care and preparation for life at home witha new baby. This study adds to our understandings of women's experiences of the early postnatal period and provides information on which to base improvements in postnatal care and maternityservices in WA and across Australia.